Arsenic Exposure During Pregnancy and Childhood: Factors Explaining Changes over a Decade - Paola Rubilar; Macarena Hirmas-Adauy; Mauricio Apablaza; Camila Awad; Xaviera Molina; María Pía Muñoz; Iris Delgado; Nicolás C. Zanetta-Colombo; Carla Castillo-Laborde; María Isabel Matute; Mauricio A. Retamal; Andrea Olea; et al. (Toxics)
Arsenic chronic exposure, particularly in its inorganic form, represents a significant public health concern. This study was conducted in Arica, the northernmost city in the country, whose inhabitants have been exposed to inorganic arsenic both naturally through drinking water and anthropogenically due to a toxic waste disposal site. We explored changes in inorganic arsenic levels in a cohort of pregnant women and their children over a decade, identifying exposure trends and their determinants. We used data on arsenic exposure through maternal urine samples during pregnancy, collected by the Health Authority between 2013 and 2016 (measurement 1), and followed up with assessments of their children in 2023 (measurement 2). Temporal changes in inorganic arsenic concentration were analyzed using the Wilcoxon Signed-Rank test, and a mixed linear regression model was employed to determine which factors contributed to urinary inorganic arsenic levels. We did not observe significant differences in mean arsenic concentrations between the two-time points (p = 0.4026). The mixed linear regression model revealed that children consuming bottled water had 8.3% lower urinary inorganic arsenic concentrations than those drinking tap water (95% CI: −15.36 to −0.54%). Additionally, children from ethnic groups had 8.64% higher inorganic arsenic concentrations (95% CI: 0.49 to 17.5%), while those with caregivers with higher education showed a 13.67% reduction (95% CI: −25.06 to −0.56%). Despite mitigation efforts, these findings underscore the ongoing risk of inorganic arsenic exposure among vulnerable populations. They further emphasize the importance of addressing natural arsenic contamination in water and implementing targeted interventions to reduce disparities associated with socioeconomic and demographic factors.